The Influence of Service Quality, Green Customer Value, and Green Brand Awareness on Green Customer Loyalty Through Customer Satisfaction Within Sidoarjo Eiger’s Customer - Firdausi, Ahmad; Yani, Muhammad; Hariasih, Misti (Jurnal Manajemen (Edisi Elektronik), 2025)
The increasing awareness of environmental sustainability has intensified competition among brands offering eco-friendly products. The wide range of green product choices makes it easier for consumers to switch from one brand to another. Therefore, companies must be able to maintain customer loyalty. This study aims to analyze the influence of Service Quality, Green Customer Value, and Green Brand Awareness on Green Customer Loyalty, with customer satisfaction as a mediating variable. This research employs a descriptive quantitative approach, with the population consisting of Eiger consumers in Sidoarjo. The sample was selected using a non-probability sampling technique with the purposive sampling method, resulting in 96 respondents. Data analysis was conducted using the Partial Least Square (PLS) method with SmartPLS 3.0 software. The results indicate that Service Quality, Green Customer Value, and Green Brand Awareness significantly influence customer satisfaction, which in turn enhances Green Customer Loyalty.